Vision 2030 and World AIDS Day 2023: Empowering Communities in HIV Research and Policy in Indonesia - Pande Putu Januraga (Public Health and Preventive Medicine Archive, 2023)
Notable challenges and accomplishments have characterized Indonesia's efforts in combating HIV AIDS. As of 2022, it is estimated that 546,573 people are living with HIV in the country, with new infections totaling 24,223 in the same year. Recent data shows a decrease in new HIV infections and AIDS-related deaths. However, there remains a concerning steady rate of new infections within the men who have sex with men(MSM) population.1 Although there have been improvements in Indonesia's HIV care cascade, particularly in achieving the first target of the 95-95-95 goals, challenges persist. In 2022, only 42% of people living with HIV (PLHIV) knew their status and were on HIV treatment, and a mere 15% of those on treatment achieved viral suppression.2 These figures highlight the necessity for strategies that are specifically tailored to meet the unique needs of different communities within the HIV AIDS landscape in Indonesia.